JACQUES LUCAN - Habiter. Ville et architecture - Montaner, Josep Maria (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
Jacques Lucan Habiter. Ville et architecture Lausanne: Editorial EPFL PRESS/Presses polytechniques et universitaires romandes, 2021. 404 pp. Softcover. Language: French. 37,50 € ISBN: 978-2-88915-406-7